Jarmark Dominikański : Gdańsk 1979 30.7.-12.8. / P. Kowalski. - Kowalski, Piotr (1950- ). (Krajowa Agencja Wydawnicza, 1979)
Plakat Jarmarku. Przy prawej krawędzi nazwisko autora, w dolnej części plakatu wymienieni organizatorzy.